PENTINGNYA PENDIDIKAN KARAKTER BAGI PESERTA DIDIK SEKOLAH DASAR DI ERA DIGITAL - Nida Aini; Encep Andriana; Siti Rokmanah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
ABSTRACT In current developments, many students use technology for entertainment and lack good morals and social skills. Therefore, character education is very important to foster a sense of responsibility for technological developments in the digital era and produce a quality generation. This research aims to find out how important character education is, especially in elementary schools in the digital era. In this research, researchers used qualitative research using descriptive methods. Researchers also used interview, observation and documentation techniques in collecting data. The results of this research show that character education has an important role in shaping the character and morals of students with the various influences of digital technology such as social media, online games, and easily accessible information.